Nupcie facte sunt: Et transreformatorisk, kontekstualiserende studie af tre prædikener til anden søndag efter helligtrekonger - Kjøller-Rasmussen, Jonas (Dansk Teologisk Tidsskrift, 2019)
The article provides a comparative study of sermons on the wedding at Cana (Second Sunday after Epiphany) from three Danish sermon collections by Peter Madsen (d. c. 1486), Christiern Pedersen (d. 1554), and Hans Tausen (d. 1561). The study draws upon methodological developments within the field of sermon studies to show the importance of a contextualizing, trans-reformation perspective: contextualizing, by referring to the context of the sermon collection in the study of the singular sermon and taking into account its purpose and compilation; trans-reformation, by referring to a selection of material from before and after the reformation in order to better understand the reception of tradition through its rejection, adaptation, and continuation. On this basis, the article argues that before and after the reformation there was general agreement in the exegesis of the pericope, but great difference in how the text was used – a difference that may partly be explained by a contextualization of the sermon.